Spider-man: the vengeance of venom ebook Vengeance of venom - special. - Michelinie, David (Marvel Worldwide, Inc., 2017)
Collects Amazing Spider-Man (1963) #332-333, #346-347, #361-363 And #374-375; Spider-Man: The Trial Of Venom and material From Amazing Spider-Man (1963) #373, #388 And Annual #25-26; Peter Parker, The Spectacular Spider-Man Annual #12; And Web Of Spider-Man Annual #8. When the web-slinger donned a sleek black costume of alien origin, he had no idea it would one day become his deadliest foe: Venom! See the misguided Eddie Brock in some of his earliest adventures as he tries time and again to take down the hated Spider-Man! Featuring the first appearance of Carnage! Plus: the Black Cat, Silver Sable and the Human Torch!